Dangerous ground : my friendship with a serial killer - Phelps, M. William (Kensington Publishing Corp., 2017)
For the first time, investigative journalist M. William Phelps reveals the identity of "Raven," the serial killer who co-starred with him on Dark minds and tells the story of his intriguing bond with one of America's most disturbing killers.